2018
DOI: 10.3389/fpsyg.2018.01929
|View full text |Cite
|
Sign up to set email alerts
|

Linking Self-Construal to Creativity: The Role of Approach Motivation and Cognitive Flexibility

Abstract: While some evidence has linked the way individuals define themselves in relation to others (independent versus interdependent self-construal) to creativity, little is known about the underlying mechanism in explaining why and how self-construal influences creativity. Integrating approach-avoidance motivation theory and the dual pathway to creativity model, this research focuses on the motivational and cognitive mechanisms that transfer the effects of self-construal on creativity. Specifically, we expect that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…We draw from both principles of career capital theory (DeFillippi & Arthur, 1994) and approach-motivation theory (Elliot, 2006;Shao et al, 2018) to elucidate the notion of distance learning employees' work world orientation in relation to their career mindsets. Individuals' approach towards a situational context is generally activated or invigorated by intrinsic motivations associated with their 'knowing why' and 'knowing what' career capitals that direct their responses towards stimuli in the external environment.…”
Section: World Of Work Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…We draw from both principles of career capital theory (DeFillippi & Arthur, 1994) and approach-motivation theory (Elliot, 2006;Shao et al, 2018) to elucidate the notion of distance learning employees' work world orientation in relation to their career mindsets. Individuals' approach towards a situational context is generally activated or invigorated by intrinsic motivations associated with their 'knowing why' and 'knowing what' career capitals that direct their responses towards stimuli in the external environment.…”
Section: World Of Work Orientationmentioning
confidence: 99%
“…'Knowing what' career capital alludes to the activation of approach-motivation that results in individuals evaluating the environment as benign and proffering positive stimuli and possibilities for achieving success (Jones & DeFilippi, 1996). Research shows links between a state of approach motivation and cognitive flexibility and originality towards external stimuli (Shao et al, 2018).…”
Section: World Of Work Orientationmentioning
confidence: 99%
“…Little research has examined the relationship between Zhongyong and creativity, and the results of a few studies have been mixed. Some research has found that employees with low levels of Zhongyong exhibit low levels of creativity because they are more rigid in their thinking, which goes against the flexibility needed for creativity (Shao et al, 2018). Similarly, some research has found a positive relationship between high levels of Zhongyong and creativity (e.g., Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is likely that middle school students who have intrinsic motivation as a personality trait may enhance their creativity by improving their cognitive flexibility. According to Shao et al (2018), flexible processing plays an essential role between a motivational approach and creativity, and Baas et al (2011a) observe that the motivational approach generally boosts creativity because it is associated with enhanced CF. Earlier researchers have highlighted the role of intrinsic motivation in creativity, but how and why IM is linked to creativity is fragmented in the existing literature.…”
Section: ) Mediating Effect Of Cognitive Alternatives and Cognitive C...mentioning
confidence: 99%